Semantische Felder der deutschen Lehnwörter im Slowenischen - Šekli, Matej (Slavica Tergestina, 2015)
In the article the semantic fields of German loan-words in Slovenian are discussed. The Slovenian-German language contact is put into a broader context of Slavic-Germanic language contacts. On the basis of the phonological characteristics of German loan-words in Slovenian the relevant geolect (i.e. the geographic variant), the sociolect (i.e. the social variant) as well as the chronolect (i.e. the temporal variant) of the German source is determined. Both phonological and semantic analyses of German loanwords in Slovenian help to expose the spheres of human culture in which the German culture exerted its influence on the Slovenian culture throughout the different historical periods.
Keywords: Bavarian High German; bavarska visoka nemščina; chronolect; fonetika; geolect; geolekt; German language; jeziki v stiku; južnobavarska visoka nemščina; kronolekt; language contact; nadomestno glasoslovje; nemščina; phonetics; semantics; semantika; Slovenian language; slovenščina; sociolect; sociolekt; Southern Bavarian High German; stično jezikoslovje; substitutional phonology